2010
DOI: 10.1158/1541-7786.mcr-09-0373
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Activation of Caspase-3 and Poly ADP Ribose Polymerase Cleavage in Fanconi Anemia Cells

Abstract: Fanconi anemia (FA) is a rare syndrome characterized by developmental abnormalities, progressive bone marrow failure, and cancer predisposition. Cells from FA patients exhibit hypersensitivity to DNA cross-linking agents and oxidative stress that may trigger apoptosis. Damage-induced activation of caspases and poly ADP ribose polymerase (PARP) enzymes have been described for some of the FA complementation groups. Here, we show the constitutive activation of caspase-3 and PARP cleavage in the FA cells without e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 46 publications
3
22
0
Order By: Relevance
“…The main known role of FA proteins is in the repair of DNA interstrand crosslinks . However, recent studies demonstrate that some other functions can be equally important, especially when dealing with cancer predisposition of FA patients . In this study we have reported for the first time elevated levels of IL‐8, MMP‐2, and MMP‐9 secretion by FAA, FAC cells and confirmed IL‐6 secretion described earlier for FA cells .…”
Section: Discussionsupporting
confidence: 88%
“…The main known role of FA proteins is in the repair of DNA interstrand crosslinks . However, recent studies demonstrate that some other functions can be equally important, especially when dealing with cancer predisposition of FA patients . In this study we have reported for the first time elevated levels of IL‐8, MMP‐2, and MMP‐9 secretion by FAA, FAC cells and confirmed IL‐6 secretion described earlier for FA cells .…”
Section: Discussionsupporting
confidence: 88%
“…A similar apoptotic response was not detected in EUFA423F cells at the concentrations and times tested, but those cells are an FA line. Cell death mechanisms in FA cells are less well-studied, and some cells constitutively produce caspase 3 and show PARP cleavage (46). Although we show evidence that the apoptotic response remains, this response might be different for BRCA lines that are not FA.…”
Section: Discussionmentioning
confidence: 99%
“…This miR-34a damage-related effect could be particularly deleterious in FA patients because of the constitutive activation of caspase3, a key enzyme for apoptosis, identified in FA cells. 26 …”
Section: Discussionmentioning
confidence: 99%